Understanding why resident doctors leave the NHS and what can be done to retain them: protocol for a realist synthesis - Geoff Wong; Karen Mattick; Priya Patel; Simon Briscoe; Daniele Carrieri; Kevin Teoh; Anna Melvin; Naomi Klepacz; Florence Katie Lock (BMJ Open)
Introduction The UK’s medical workforce is under increasing strain, and this is compounded by increasing numbers of resident doctors diverging from specialist training pathways, instead entering non-training roles, reducing clinical hours or leaving the profession or UK workforce entirely. These decisions are shaped by both individual motivations and wider structural conditions, including unsatisfactory working conditions, limited flexibility and a perceived lack of support or autonomy. While pursuing alternative career routes offers personal and professional benefits, they can also delay progression to senior clinical roles, contributing to workforce instability. There remains limited understanding of how best to support retention, particularly given the varied contexts, settings and career trajectories of resident doctors. This realist synthesis will examine how, why and in what contexts resident doctors leave the National Health Service, and what interventions might support their retention.Methods and analysis This realist synthesis will follow Realist And Meta-narrative Evidence Synthesis: Evolving Standards guidance and will be conducted in five iterative steps: (1) identifying existing theories to develop an initial programme theory; (2) undertaking formal and purposive searches to identify relevant UK-based literature; (3) selecting documents based on relevance and rigour; (4) extracting and coding data to support the development of explanatory insights; and (5) synthesising findings using a realist logic of analysis to develop and refine context-mechanism-outcome configurations. An advisory group will guide the review throughout. The final programme theory will inform the development of evidence-based recommendations and design principles to support resident doctor retention.Ethics and dissemination Ethical approval is not required for this synthesis of existing literature. Findings will be disseminated through academic publications, conference presentations and accessible formats, including infographics, plain English summaries and blog posts. Target audiences include resident doctors, medical educators, workforce planners and policymakers.Study registration PROSPERO, CRD420251004453.